2020
DOI: 10.3989/loquens.2020.072
|View full text |Cite
|
Sign up to set email alerts
|

The perception of multiethnolectal Zurich German: A continuum rather than clear-cut categories

Abstract: Since about 2000, the emergence of so-called ‘multiethnolects’ has been observed among adolescents in German-speaking Switzerland; however, a systematic description of these varieties is lacking at present. The few existing perception studies of multiethnolects in other European countries are usually based on two or more predetermined groups that are compared. This paper investigates which labels are used for multiethnolectal Zurich German and how this way of speaking is perceived by adolescents; we adopt a pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
0
1
0
Order By: Relevance
“…To be sure, the results display convergence but do not tell anything about whether G3 speakers from Zurich apply the same strategies as their non-migrant-background Swiss German peers nor how they perform in terms of morphology and lexicon. We do not know to what extent our G3 participants differ from speakers of the other majority language and/or possibly converge on an ethnolectal variety of (Swiss) German (Tissot, Schmid, and Galliker, 2011;Morand, Schwab, and Schmid, 2020). A qualitative assessment of the Swiss German versions of the renarration by non-migrant-background speakers does not endorse the assumption that G3 speakers differ substantially from native performance.…”
Section: Discussionmentioning
confidence: 79%
“…To be sure, the results display convergence but do not tell anything about whether G3 speakers from Zurich apply the same strategies as their non-migrant-background Swiss German peers nor how they perform in terms of morphology and lexicon. We do not know to what extent our G3 participants differ from speakers of the other majority language and/or possibly converge on an ethnolectal variety of (Swiss) German (Tissot, Schmid, and Galliker, 2011;Morand, Schwab, and Schmid, 2020). A qualitative assessment of the Swiss German versions of the renarration by non-migrant-background speakers does not endorse the assumption that G3 speakers differ substantially from native performance.…”
Section: Discussionmentioning
confidence: 79%
“…In a previous study on read speech, we found slower syllable rates in speakers of rather multiethnolectal Zurich German (MEZ) compared to speakers of rather traditional Zurich German [24]. Based on a rating experiment, adolescents could be placed on a perceptual continuum between multiethnolectal and traditional Zurich German [25]. It now remains to be seen whether syllable rate also proves to be linked to multiethnolectality in spontaneous speech and thus could be classified as a general prosodic feature of MEZ.…”
Section: Introductionmentioning
confidence: 79%
“…To obtain an 'emic' perspective [37] -i.e., as from inside the cultural system of MEZ -we conducted a 'rating experiment' with a different, but very similar group of adolescents [25].…”
Section: Rating Scoresmentioning
confidence: 99%